Rol de la familia en el desarrollo cognitivo de los niños de nivel inicial - Villacis Paz, Arelis Adriana (2023)
The following investigation entitled Role of the family in the cognitive development of children of initial level, was carried out in the Escuela de Educación Básica Fiscomisional "Padre José Antonio González de Durana" due to lack of knowledge on the part of the parents about the how to help develop cognition in their constituents, the context of the school is a place of great vulnerability located in the Durán Canton Km 9 ½ Vía Durán Yaguachi in the Ciudadela el Recreo of stage 4. Of mixed approach methodology, since conforms to the study of qualitative and quantitative, inductive-deductive and synthetic analytical methods, present within the pedagogical model chosen to reach significant knowledge, oriented through the observation of the facts, we will start from a brief explanation, what are these methods for your better interpretation and practice. The following contributions of the research will help to solve the mentioned problem through the elaboration of a workshop guide aimed at parents, with the purpose of facilitating awareness, information and execution strategies, which can be put into practice in their daily lives. for children's cognitive development. Concluding that the parents were able to equate and identify the roles that each of the families have in the home, for them it was very relevant, since it allowed them to have a more objective look at their family reality, it is essential to mention that it is a role inescapable that families have as the main educator of their children.